O ensino das partículas elementares a partir de uma sequência didática - Moura Júnior, Orlando Leite de (2020)
In this academic work we present the development of the study, elaboration, application and verification of the data of a Didactic Sequence (SD) that aims to assist students learning in the third year of high school (EM), in a state public school in the interior of São Paulo. The content to be studied are the Elementary Particles (PE) – basic components of matter – and their interactions, an integral part of the theme of Modern and Contemporary Physics (FMC). The SD was supported by the Theory of Meaningful Learning (TAS) and by the State of São Paulo High School Curriculum. The pedagogical activities present on the SD are clarified in four distinct Didactic Units (UD) that aim to mitigate the apparent difficulties of teaching and learning contents related to the subject of Physics, mainly FMC. The activities were followed by formative and summative assessments (taken at the end of the SD). We thus hope to be pertinent to the pedagogical context and to contribute to the continuous search for an increasingly adequate and effective teaching/learning relationship.